FTIR AND NMR STUDIES OF ADSORBED CETHYLTRIMETHYLAMMONIUM CHLORIDE IN MCM-41 MATERIALS - Paulina Taba; Russell F. Howe; Graine Moran (Universitas Gadjah Mada, 2008)
The high use of surface-active agents (surfactants) by industry and households today leads to environmental pollution, therefore treatments are required to remove such substances from the environment. One of the important and widely used methods for removal of substances from solution is adsorption. In this research, MCM-41 and its modified product of MCM41-TMCS were used to adsorb cationic surfactants, cethyltrimethylammonium chloride, CTAC. FTIR and NMR methods were used to study the interaction between the surfactants and the adsorbents. MCM-41 was synthesized hydrothermally at 100 oC and its modification was conducted by silylation of MCM-41 with trimethylchloro silane (MCM41-TMCS). Both unmodified and modified MCM-41 can adsorb the surfactant. The interaction of CTAC with MCM-41 was mostly the electrostatic interaction between the electropositive end of the surfactant and MCM-41, whereas in modified MCM-41 hydrophobic interactions become more dominant. These hydrophobic interactions appear however to involve the methyl groups on the head group of the surfactant interacting with the modified surface.